Exploring the influence of tenacity, competence and spirituality on conflict management among youth in Malaysia - Mohamad, Mua’azam; Yusoff, Zuraidah Juliana Mohamad; Yusoff, Yus’aiman Jusoh @; Jaafar, Fauziah Md; Zolkipli, Noor Haifa (Nurture, 2023)
Purpose: Youths must overcome multiple challenges to adjust to a combative environment. Resilient individuals may overcome all negative thoughts and attitudes when confronted with difficulty. However, students who are unable to change or control the conflict will have a negative attitude throughout their lives. Thus, this study aimed to examine the influence of the resilience construct on conflict management among youths in Malaysia. Design/Methodology/Approach: This study used a quantitative approach through a questionnaire instrument involving a total of 533 respondents among youths comprising students of educational programme and novice teachers in the northern zone of Peninsular Malaysia. The Connor-Davidson Resilience Scale and Rahim Organizational Conflict Inventory (ROCI II) questionnaires were used in this study. The data was analyzed using Statistical Package for the Social Sciences (SPSS) version 28 and Structural Equation Model-Part Least Square, SmartPLS 4 software. Findings: The findings showed that there was an influence of the resistance dimension on conflict management. The findings also showed that tenacity and spiritual dimensions have an influence on conflict management. Conclusion: Resilience is a skill that should be learned and possessed by each individual especially youths when facing life conflicts. Research Limitation: The data found in this study were based on questionnaires. The findings of the study were limited as they depended on the honesty and willingness of the respondents to answer the questionnaire. Contribute to the Literature: This study contributes to the existing literature that resilience constructs have influence on conflict management among youths.